History of the Welsch House, heritage of the historical Center of lima - Barrera Camarena, Henry (2019)
The present study consists of revaluing the historical and architectural importance of the Welsch House, a shop of German origin, dedicated to the sale of jewelry and watches in Lima in the mid-nineteenth century. Through the compilation of unpublished images and information, one will be able to learn more about its transformation from the time of its construction to the restoration project that was carried out in 2012. One of its best features is the famous front clock that for many years fronted the property and provided the official time to all people who passed through Jirón de la Union, the street where it was located; it was removed from original location at the end of the last century. For this reason, the study highlights its historical value, so that it may be recognized and assimilated by society. As well, the purpose of this work is to contribute to the diffusion of this monument as a part of the Historic Center of Lima.